Effects of the Toxicity of the Pesticides Maneb and Chlorpyrifos-Ethyl on a Freshwater Fish, Oreochromis niloticus - Levis Gapessie Ntiendjui; Simon Awafor Tamungang; Ferdinand Ngoula; Gilbert Ateufack; Joseph Tchoumboue (Advanced Research in Biological Science Vol. 6, 2023)
Maneb and Chlorpyrifos-Ethyl are pesticides used in large quantities in food crops in Cameroon. To assess the toxicity risks and their negative influence on aquatic biodiversity, acute toxicity bioassays on Oreochromis niloticus individuals were carried out separately with six concentrations (0; 1.80; 1.85; 1.90; 1.95 and 2 mg/l) of Maneb and (0; 0.15; 0.16; 0.17; 0.18 and 0.19 mg/l) of Chlorpyrifos-Ethyl in three replicates in static media in aquaria for 24 hours. Minimum (20.00 ± 0.00 %) and maximum (100.00 ± 0.00 %) mortalities were recorded on fisheries (mean size 3.86 ± 0.04 cm and mean weight 0.74 ± 0.02 g) with 1.85 and 2 mg/l Maneb and 0.15 and 0.19 mg/l Chlorpyrifos-Ethyl respectively. Correlations (r = + 0.96 for Chlorpyrifos-Ethyl and r = + 0.98 for Maneb) were positive and strong between mortality rates and concentrations. The 50% lethal concentration for 24 hours of exposure (LC50-24h) was relatively high with Maneb (1.93 mg/l) and low with Chlorpyrifos-Ethyl (0.154 mg/l) which is the most toxic pesticide and which also induces a particular habitus in surviving fish.